(untitled) (The Research of Medical Science Review, 2025)
Coronary Artery Disease (CAD) remains a leading cause of morbidity and mortality globally, with early detection and risk stratification critical for effective management. Serum markers such as Gamma-Glutamyl Transferase (GGT) and Aspartate Aminotransferase (AST) have been linked to systemic inflammation and oxidative stress, key contributors to CAD. This research aims to explore the association between elevated GGT and AST levels with CAD, potentially offering new biomarkers for early detection and risk assessment. Methods: This comparative cross-sectional study involved 240 participants selected through stratified random sampling to include both coronary artery disease (CAD) and non-CAD patients. The research was conducted at Adil Diagnostic Center, Rawalpindi, from September to December 2024, following ethical approval. Results: The results of the study show that a family history of Coronary Artery Disease (CAD) significantly correlates with higher prevalence rates of CAD in the study population. Patients with a positive family history and other risk factors exhibited elevated levels of Aspartate Aminotransferase (AST), Gamma-Glutamyl Transferase (GGT), and other liver parametrs such as Alkaline Phosphatase (ALP), Alanine Aminotransferase (ALT), and Total Bilirubin in CAD group as compared to Control group. Conclusion: This study demonstrates the substantial correlation between coronary artery disease (CAD) and risk factors, including high blood pressure, diabetes, smoking, high cholesterol. It also demonstrates the obvious link between CAD and liver enzyme levels, particularly GGT and AST. Elevated GGT levels have been associated with the severity of CAD and have been identified as an independent risk factor for the condition. This emphasises how crucial it is to diagnose and treat CAD while taking into account both conventional risk factors and liver health.